Anterolateral Tenodesis or Anterolateral Ligament Complex Reconstruction: Effect of Flexion Angle at Graft Fixation When Combined With ACL Reconstruction. (November 2017) - Inderhaug, Eivind; Stephen, Joanna M.; Williams, Andy; Amis, Andrew A.
Background: Despite numerous technical descriptions of anterolateral procedures, knowledge is limited regarding the effect of knee flexion angle during graft fixation. Purpose: To determine the effect of knee flexion angle during graft fixation on tibiofemoral joint kinematics for a modified Lemaire tenodesis or an anterolateral ligament (ALL) complex reconstruction combined with anterior cruciate ligament (ACL) reconstruction. Study Design: Controlled laboratory study. Methods: Twelve cadaveric knees were mounted in a test rig with kinematics recorded from 0° to 90° flexion. Loads applied to the tibia were 90-N anterior translation, 5-N·m internal tibial rotation, and combined 90-N anterior force and 5-N·m internal rotation. Intact, ACL-deficient, and combined ACL plus anterolateral-deficient states were tested, and then ACL reconstruction was performed and testing was repeated. Thereafter, modified Lemaire tenodeses and ALL procedures with graft fixation at 0°, 30°, and 60° of knee flexion and 20-N graft tension were performed combined with the ACL reconstruction, and repeat testing was performed throughout. Repeated-measures analysis of variance and Bonferroni-adjusted t tests were used for statistical analysis. Results: In combined ACL and anterolateral deficiency, isolated ACL reconstruction left residual laxity for both anterior translation and internal rotation. Anterior translation was restored for all combinations of ACL and anterolateral procedures. The combined ACL reconstruction and ALL procedure restored intact knee kinematics when the graft was fixed in full extension, but when the graft was fixed in 30° and 60°, the combined procedure left residual laxity in internal rotation ( P = .043). The combined ACL reconstruction and modified Lemaire procedure restored internal rotation regardless of knee flexion angle at graft fixation. When the combined ACL reconstruction and lateral procedure states were compared with the ACL-only reconstructed state, a significant reduction in internal rotation laxity was seen with the modified Lemaire tenodesis but not with the ALL procedure. Conclusion: In a knee with combined ACL and anterolateral ligament injuries, the modified Lemaire tenodesis combined with ACL reconstruction restored normal laxities at all angles of flexion for graft fixation (0°, 30°, or 60°), with 20 N of tension. The combined ACL and ALL procedure restored intact knee kinematics when tensioned in full extension. Clinical Relevance: In combined anterolateral procedure plus intra-articular ACL reconstruction, the knee flexion angle is important when fixing the graft. A modified Lemaire procedure restored intact knee laxities when fixation was performed at 0°, 30°, or 60° of flexion. The ALL procedure restored normal laxities only when fixation occurred in full extension.